The Effectiveness of Physical Exercise in Stroke Patient Recovery: A Systematic Review - Denny Christian Lukas; Williem Harvey; Meilisa Sri Suzana (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Stroke is a leading cause of disability worldwide, significantly affecting motor function, mobility, and patients’ quality of life. Physical exercise is often recommended as part of rehabilitation programs to enhance recovery after a stroke.  Objective: This study aims to systematically review the literature on the effectiveness of physical exercise in accelerating post-stroke recovery, particularly in improving motor function, mobility, and independence.  Methods: A systematic search was conducted across electronic databases such as PubMed, Scopus, and ScienceDirect using keywords like "stroke rehabilitation," "physical exercise," "motor recovery," and "systematic review." Inclusion criteria covered articles published in the last 10 years, in English or Indonesian, involving post-stroke patients undergoing physical exercise programs. The articles were analyzed to evaluate the type of exercise, frequency, duration, and clinical outcomes.  Results: Fifteen articles met the inclusion criteria. Aerobic exercise, strength training, and task-oriented therapy were found effective in improving motor function and mobility in stroke patients. Exercise programs performed intensively for a minimum of 4 weeks showed significant results compared to conventional therapy. Positive effects were also observed in patients’ quality of life. Conclusion: Physical exercise has been proven effective in facilitating stroke recovery, especially when individually tailored and performed regularly. This study recommends implementing standardized physical exercise-based rehabilitation programs to support post-stroke recovery.